The role of virtual and augmented reality in orthopedic trauma surgery: From diagnosis to rehabilitation. (July 2020) - Negrillo-Cárdenas, José; Jiménez-Pérez, Juan-Roberto; Feito, Francisco R.
Highlights: An exhaustive review of orthopedic trauma surgery applications is performed, delving into each step, from diagnosis to rehabilitation. For each defined task, current application of viral and augmented reality, their usefulness, weakness and future trends are detailed. A qualitative set of indicators is provided to highlight open research line to introduce new researchers in this field. Graphical abstract: Abstract: Virtual and augmented reality have been used to assist and improve human capabilities in many fields. Most recent advances allow the usage of these technologies for personal and professional purposes. In particular, they have been progressively introduced in many medical procedures since the last century. Thanks to immersive training systems and a better comprehension of the ongoing procedure, their main objectives are to increase patient safety and decrease recovery time. The current and future possibilities of virtual and augmented reality in the context of bone fracture reduction are the main focus of this review. This medical procedure requires meticulous planning and a complex intervention in many cases, hence becoming a promising candidate to be benefited from this kind of technology. In this paper, we exhaustively analyze the impact of virtual and augmented reality to bone fracture healing, detailing each task from diagnosis to rehabilitation. Our primary goal is to introduce novel researchers to current trends applied to orthopedic trauma surgery, proposing new lines of research. To that end, we propose and evaluate a set of qualitative metrics to highlight the most promising challenges of virtual and augmented reality technologies in this context.